Pengaruh Prestasi Belajar PAI, Penggunaan Media Sosial, dan Kecerdasan Emosional Terhadap Akhlak Peserta Didik MTss Miftahiyah Yasi Bangkalan - Al Mursyidi, Busro Muhammad; Muhammad Yusron Maulana El-Yunusi; Didit Darmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education is an effort that seeks to convey information through guidance, direction and training both inside and outside educational institutions in order to educate students to contribute to their future lives. This involves the growth of knowledge, moral principles, and ethics such that higher levels of education reflect not only academic proficiency but also the capacity to acquire moral principles through appropriate education. The aim of this research is to determine the influence of Islamic Religious Education (PAI), use of social media, and emotional intelligence on the moral growth of MTs Miftahiyah Yasi Bangkalan students. Data was collected through the use of questionnaires and observations of 75 students. The findings of the regression analysis show that students' moral behavior is significantly influenced by the use of social media, emotional intelligence, and academic achievement in Islamic Religious Education. These findings expand our understanding of how Islamic religious teaching, social media, and emotional intelligence interact to shape students' moral growth in the digital era.